Perancangan Buku Ilustrasi Mengenai Sejarah Candi Badut Untuk Memberikan Informasi Sejarah Kepada Masyarakat Kota Malang - Stya Bakti, Amar Ma'ruf; Irianto, Mahardika Christian; Sukmaraga, Ayyub Anshari (LPPM STIKI Malang, 2025)
Indonesia has a rich and diverse historical heritage, but some aspects remain unclear in terms of their origins, such as Candi Badut in Malang Regency. The lack of information about the history of this temple makes it an interesting topic to explore, encouraging the people of Malang to learn more about it. Therefore, an illustrated book is designed as an engaging way to present the history of Candi Badut to the target audience aged 18 and above. This design uses a qualitative method through observation and literature study for data collection, and it applies the ADDIE design model with a cyclic strategy. The outcome of this design is an A5-sized illustrated book featuring oil painting-style illustrations and chiaroscuro lighting techniques. Supporting merchandise includes hats, tote bags, mugs, tumblers, and t-shirts, while promotional media consist of banners, posters, and acrylic displays. Evaluation results show that the book is easy to understand and appealing to read.